Energy Access among the Urban Poor in Kenya: A Case Study of Kibera Slums - Lesirma, Simeon (International Journal of Environmental Sciences, 2016)
Purpose: The bulk of the population in developing countries is poor and survives on nonâˆ’commercial energy sources such as fuel wood, agricultural residues or animal dung which are the most easily available and can be gathered at almost zero private cost. The general objective of the study is to carry out a study on energy access among the urban poor; a case study in Kibera slums. The specific objectives were to establish the commonly used sources of energy by households living in Kibera slums, to determine the factors influencing the use/adoption of particular energy sources by households living in Kibera slums and lastly to assess the environmental impacts of the use/adoption of particular energy sources by households living in Kibera slums. Methodology: The study used a literature review/desktop research. Findings and Conclusions: The findings of the empirical review demonstrate that kerosene, electricity, biomass and LPG play an important role in cooking and lighting in low-income areas such as Kibera, Nairobi. According to the findings, kerosene is the most important modern energy option for the poor for both lighting and cooking. Electricity also appears to be a relatively important energy option. Biomass, charcoal and LPG as sources of energy appear to be consumed by a relatively small segment of the urban poor in the selected sample area services among the urban poor. The paper established that the factor that influence the adoption of various types of energy source include level of knowledge and awareness, level of income of households, and availability of substitute power. Results also indicated that the most obvious environment problems associated with charcoal production and use was the extent of vegetation and forest clearing estimated to range from 0.087 to 1.33 million hectares, depending of the sources of the wood. In addition, heavy dependence on wood for fuel has contributed to the rapid decline of Kenya's forests, with negative effects for the local climate, wildlife, water sources and forest dwellers, says the World Rainforest Movement. Recommendations: The study recommends that Government should establish a dedicated institution similar to the Rural Electricity Authority, with the specific mandate of expanding the urban poor's access to modern energy services. As with the rural electrification programme, a levy in electricity and liquid fossil fuels can be a reliable source of finance for urban poor access programme.